Corporate dividend policies in bank-based and market-based systems : survey evidence from UK and Portugal - Archbold, Stuart (2010)
This paper reports the empirical results of a questionnaire survey about corporate dividend policy addressed to finance directors of UK and Portuguese listed firms. Similar to other studies (for example, Brav et al., 2005 in the US and Dhanani, 2005 in the UK), we survey 313 finance directors in the UK and 48 in Portugal to examine their views of and understanding about the dividend decision in order to compare practice with theoretical propositions to be found in the literature and to examine cross-country determinants of dividend policy. Our survey results demonstrate similarities in the responses from the UK and Portugal, but also substantive differences, particularly in respect of the interaction between dividend and investment decisions and views about the signalling consequences of dividends.